Policy Direction for Strengthening Accountability and Transparency in the Management of Direct Grant Receipts at BMKG - Syafridawati, Syafridawati (Center for Maritime Policy Governance Studies (CMPGS), 2025)
The Meteorology, Climatology, and Geophysics Agency (BMKG) increasingly relies on external grants both cash and in kind to strengthen early warning, forecasting, and service delivery, yet recurring administrative irregularities in grant receipt and management continue to generate audit exposure and weaken the reliability of institutional reporting. This study aims to examine why grant governance problems persist despite an established legal framework and organizational responsibility structure, and to identify policy options that can improve transparency, accountability, and rule-of-law compliance in BMKG’s grant governance. Methodologically, the research employs a qualitative, descriptive case-study approach with a policy and governance analysis orientation, drawing on a combination of document review (regulations, internal guidelines, and relevant administrative records) and stakeholder perspectives from organizational units involved in planning, finance, asset management, procurement, and internal oversight. Data were analyzed through thematic content analysis using good-governance principles as analytical benchmarks, complemented by a root-cause perspective and a SOAR-based evaluation to assess strengths, opportunities, aspirations, and results for reform implementation. The findings show that the most critical gaps are not merely normative but operational: fragmented workflows, delayed and uneven reporting practices, limited procedural literacy among implementers, and weak enforcement mechanisms often compounded by non-integrated systems and manual workarounds that reduce traceability and undermine documentation quality. The study further finds that isolated interventions are insufficient; improvements in socialization alone will not sustain compliance without standardized operational guidance and enforceable accountability.